1975
DOI: 10.1088/0029-5515/15/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Losses of a thermonuclear plasma imploded by a high-velocity wall

Abstract: Energy losses occurring in high-temperature plasma in contact with a rapidly moving wall are studied. It is found that thermal-conduction and radiation losses prevent reaching thermonuclear temperatures unless the wall moves at a very high speed. On the other hand, re-absorption in high-density systems and relatively weak magnetic fields reduce these losses. A thermonuclear regime can be reached with wall velocities of 25 km/s, attainable by electromagnetic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Our model therefore describes the energy dynamics of the inner hot core, when it exists. The preceding study [1] has shown that such a core can be maintained with a sufficiently rapid liner, a sufficiently high magnetic field, provided that the experiment stays away from the radiative regime v/here bremsstrahlung losses become excessive. This last condition is written as…”
Section: As In Refmentioning
confidence: 96%
See 2 more Smart Citations
“…Our model therefore describes the energy dynamics of the inner hot core, when it exists. The preceding study [1] has shown that such a core can be maintained with a sufficiently rapid liner, a sufficiently high magnetic field, provided that the experiment stays away from the radiative regime v/here bremsstrahlung losses become excessive. This last condition is written as…”
Section: As In Refmentioning
confidence: 96%
“…[l], we study the implosion of a weakly magnetized dense plasma (j3» 1, n~10 m" , T~ 100 eV) by a rapidly moving liner (v~20 km-s' 1 )…”
Section: As In Refmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Because of the small gain of MTF, the author had suggested to use MTF as a booster stage for the ignition of second high gain inertial confinement fusion targets. 5 In Thio et al 's new approach towards MTF, a quasispherical array of plasma jets is focused onto a small volume into which the magnetized deuterium-tritium ͑DT͒ fusion target is placed.…”
Section: Introductionmentioning
confidence: 99%
“…II-l, fresh liner/leads assemblies [1] coming from a refabrication facility (not shown) are transported to the FLR core as spent liner/leads assemblies [2], and are removed for reprocessing by the rotating liner manipulator [3]. A liner/leads assembly is inserted through a port in the blast-containment header, and the plasma source and the connector module for the energy transfer and storage (ETS) system [4], which is attached to the external ETS leads arm [5J, is moved into place [6l The liner/leads assembly is clamped to the containment vessel by a latching assembly [7]. The M50-MJ power supply consists of a bank of homopolar generators [8], an intermediate storage inductor, intermediate transfer capacitors and switches [9], all of which are shown approximately to scale.…”
mentioning
confidence: 99%